Nutritional Optimization: Chronic Energy Deficiency Intervention for Pregnant Women by Consuming Sandwich Biscuits and Chicken Eggs - Sirait, Lenny Irmawaty; Nurhidayah, Munda Bay; Aritonang, Tetty Rina (Jurnal Bidan Cerdas, 2024)
Introduction: Chronic Energy Deficiency (CED) is a prolonged nutritional condition resulting from insufficient energy intake, which can increase the risk of anemia, preeclampsia, infections, and impaired fetal growth. CED also contributes to preterm birth, low birth weight (LBW), and congenital anomalies and raises the risk of cognitive decline and chronic diseases later in life. Objective: To explore the effectiveness of nutritional optimization through consuming sandwich biscuits and boiled eggs among pregnant women with CED. Method: This study employed a true experimental design with two pretest-posttest groups, involving 20 pregnant women in their second and third trimesters with CED. The intervention group (n=10) consumed 3 sandwich biscuits and 2 boiled eggs daily, while the control group (n=10) consumed 3 sandwich biscuits daily, both for 30 days. Measurements included upper arm circumference (UAC) and body weight (BW), analyzed using independent t-tests and paired t-tests. Results: The intervention group showed a significant increase in UAC (from 22.1 to 23.9 cm) and BW (from 43.2 to 45.4 kg), with mean differences of 1.8 cm and 2.2 kg, respectively (p=0.000). The control group also showed significant increases in UAC (from 22.2 to 23.6 cm) and BW (from 43.8 to 45.3 kg), with mean differences of 1.4 cm and 1.5 kg, respectively (p=0.000). Conclusion: The combined consumption of sandwich biscuits and boiled eggs significantly improves UAC and BW, indicating its potential to reduce CED risk in pregnant women. Further research is needed to understand better CED, particularly in relation to UAC and BW changes.